A Free-Radical and Protecting-Group-Free Approach to (–)-Boschnialactone and γ-Lycorane - Basante-Avendaño, Alberto; Guerra-Ayala, Víctor E.; Sánchez-Eleuterio, Alma; Cordero-Vargas, Alejandro (Synthesis, 2019)
The protecting-group-free (PGF) and free-radical-based synthesis of two structurally different natural products, (–)-boschnialactone and γ-lycorane, is reported. The key step in both syntheses is a radical–ionic sequence for construction of the principal structure (a six-membered lactone and a 1,4-dicarbonyl compound, respectively), allowing short and rapid access to these natural products through a PGF route.
Keywords: radicals; protecting-group-free synthesis; atom-transfer radical addition; ATRA; boschnialactone; lycorane